Investigation of some physical and structural properties of melts by ultrasounds - Kazhikenova, S.Sh.; Shaikhova, G.S.; Shaltakov, S.N. (Karagandy University of the name of acad. E.A. Buketov, 2025)
A modern effective way of influencing molten metal is ultrasonic treatment - a type of dynamic influence on liquid and crystallizing metal. At certain parameters of the intensity of ultrasonic treatment, which causes acoustic cavitation of the liquid metal, the refining process actively occurs. Moreover, powerful ultrasound allows, during the modification process, to introduce various composite elements and refractory alloys into the metal, acting directly on the crystal lattice. The calculations carried out on the properties of elastic waves make it possible to identify such features in the behavior of the sound absorption coefficient polytherms, which with sufficient certainty indicate the absence or presence of structural changes when the melt is heated, and establish the possibility of implementing various mechanisms of structural changes in the same melt in different temperature ranges. The conducted studies of elastic wave energy absorption as well as ultrasound velocity allow us to identify such features in the behavior of sound absorption coefficient polyterms that indicate the absence or presence of structural changes during melt heating. The comparative analyses make it possible to conclude that there is not a single mechanism of structural changes The possibility of implementing various mechanisms of structural changes in the same melt in different temperature ranges is shown.
Keywords: viscous; liquid metals; ultrasound propagation speed; structural changes; melt